The last Mandarin - Penny, Louise; Fung, Mellissa, 1972- (Minotaur Books, 2026)
"Alice Li, a first-generation Chinese-American, is an erstwhile food blogger who has lived in the shadow of her mother, Vivien Li. A Chinese dissident who escaped China after Tiananmen Square, Vivien is now a globally recognized human rights activist and passionate advocate for a free and democratic China. When security and fire alarms go off simultaneously all around the world, setting off a panic, the signal is traced back to China. As world leaders scramble to respond, Vivien and Alice are called to the White House in hopes Madame Li can decode the Chinese intentions. While it makes some sense that the President would turn to Vivien, since she regularly advises world leaders on the actions of today's Chinese government, what isn't clear is why they'd want to talk to Alice. After looking at the evidence, Vivien says that the only thing worse than the Chinese government being behind it, is if they are not. It would mean, she explains, that some clandestine element within China is calling the shots. That the President of China has lost control. And an unstable China cannot be good for anyone. Or perhaps that's exactly what the shrewd old politician wants everyone to think. Caught up in the chaos, Vivien and Alice are uniquely placed to stop the next, cataclysmic attack. But there are forces deep within both the American and Chinese governments intent on stopping mother and daughter. The estranged pair, who excels at misunderstanding each other, must figure out how to work together. The increasingly frantic search for answers takes the women from the Oval Office to an office building in Akron, Ohio, from the noodle shops of Hong Kong to the necropolis of the first emperor. Along the way they must decode an old legend, and an old language invented by women, for women." --